2010
DOI: 10.1007/s11126-010-9151-1
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perspectives About Brief Psychiatric Hospitalization: What is Helpful and What is Not?

Abstract: Significant numbers of adolescents receive inpatient psychiatric services, yet we know little about their experiences: what about hospitalization is perceived as helpful and what is counter-productive or even harmful? In this study, eighty adolescents hospitalized for the first time in a psychiatric program were interviewed within a week of discharge (using a semi-structured interview format), and asked to describe what did and did not help them. Multiple themes emerged relating to helpful experiences and thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 39 publications
(77 reference statements)
4
58
0
2
Order By: Relevance
“…People who believed detention was necessary recognised they were self-destructive and were happy for professionals to take control. They believed that structure and routine helped create a sense of sanctuary, which is a finding supported by previous research (Moses, 2011). Humane aspects of care was a theme similar to those which emerged in Katsakou and Priebe's (2007) review, and included factors which promote a more positive experience of detention.…”
Section: Discussionsupporting
confidence: 52%
“…People who believed detention was necessary recognised they were self-destructive and were happy for professionals to take control. They believed that structure and routine helped create a sense of sanctuary, which is a finding supported by previous research (Moses, 2011). Humane aspects of care was a theme similar to those which emerged in Katsakou and Priebe's (2007) review, and included factors which promote a more positive experience of detention.…”
Section: Discussionsupporting
confidence: 52%
“…There should be dedicated areas where therapy or activity groups, for example, can be conducted that are separate from the areas where the adolescents can go to be on their own. Moses (2011) reports in his study that some adolescents stated that they felt safe in an environment where there was much structure because it distracted them from their troubles and thus prevented them from acting out distressing thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Ellilӓ et al (2007) and Gatta et al (2010) observe that developing a satisfying interpersonal relationship between the professional and the adolescent, is the 'raison d'être' for inpatient hospital therapy. According to a study undertaken by Moses (2011), adolescents found that having meaningful interpersonal relationships with staff members was one of the most helpful aspects of being part of an inpatient hospital programme. Several studies (Grossoehme and Gerbetz 2004, Bobier et al 2009, Moses 2011 indicate that what adolescents found beneficial about being admitted to a psychiatric hospital and being part of a therapy programme, was the personal interaction with the personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the academic and therapeutic communities overseas have documented various facets of this phenomenon (e.g. Bettmann & Jasperson, 2009;Hayes et al, 2011;Moses, 2011a), it appears that Australia has yet to offer any robust qualitative research. This is significant as some Australian surveys suggest that up to one quarter of adolescents may experience mental health difficulties, while only less than 1 in 3 may attempt at getting help (Sawyer et al, 2007;Zubrick et al, 2000).…”
Section: Contribution To Knowledgementioning
confidence: 99%